FACTORS OF HEALTHY AGING: A LITERATURE REVIEW (Fiep Bulletin - online, 2011)
The discussion of successful aging is relatively new, one of the topics widely disseminated among the media, services, research and texts that instruct law and public policy in the field of gerontology. In this area, it is assumed that the clock time must be increased by active life, identified as a need of work handled in recent years, largely related to increased production in science, technology and practices of health care for the elderly. This study aimed to identify the literature the factors related to human aging process healthy considering the increase in the number of people over 60 years in Brazil. Methods: This descriptive and exploratory study conducted by reviewing the literature, taking as the database for the Scientific findings in the period between the months of August and September 2009. Results and Discussion: The findings showed that one of the strategies to leverage the gains of the aging process would be the quest for healthy aging, the result of a series of activities encouraged with a view to promoting health, preventing or delaying the installation of chronic conditions, slowing functional decline, encouraging their autonomy and independence. Thus, it preserved the cognitive aspect of social integration and enhancement of interpersonal relationships and affective. Conclusion: We highlight the importance to seek new forms of assistance to enable them to reduce the losses that course, and that the population can reach old age with quality of life engaged in a variety of key factors that involve individuals, families, governments and public health. Thus, we need public policies that are directed specifically to this age group, which should be designed and implemented with care and urgency, in view of healthy aging.
Keywords: active aging; healthy aging and aging population